Results of a comprehensive assessment of the health status of children after a new coronavirus infection (COVID-19) - I. K. Bogomolova; A. A. Babkin; V. N. Peregoedova (Журнал инфектологии, 2024)
The inhabitants of the planet in the XXI century are experiencing a second pandemic. The new coronavirus SARSCoV-2 is distinguished not only by its ubiquitous spread, but also by the possibility of developing adverse outcomes, which does not cause anyone doubts today.Aim. To present the dynamic characteristics of children’s health depending on the form of severity of the new coronavirus infection (COVID-19).Material and methods. A prospective single-center clinical study of the complex state of health of children hospitalized in a monoinfective hospital on the basis of the GUZ “City Clinical Hospital” was conducted. The observation included 86 convalescents of a new coronavirus infection aged 7 to 14 years. Dynamic monitoring was carried out for children for 1.5 years from the moment of infection with SARSCoV-2, control visits were performed 1, 6 and 18 months after the disease.Results and discussion. According to the results of a comprehensive assessment of the health status of children after COVID-19, an increase in the number of registrations of recurrent upper and lower respiratory tract infections in convalescents of a moderate form of a new coronavirus infection was found. In 35 (41%) children after infection with SARSCoV-2, concomitant diseases were recorded, in contrast to 23 (26.7%) cases recorded before the pandemic. The structure of concomitant pathology in COVID-19 convalescents is represented by endocrine pathology in 30.2% of cases, in patients after moderate forms of the disease, the frequency of eating disorders (19.8%) increased by 2 times relative to the period before COVID-19, type 1 diabetes mellitus was first detected in 1 (1.2%) child. Diseases of the nervous system (20.9%) were 1.9 times more likely to be diagnosed after COVID-19. Diseases of the eye and its accessory apparatus were registered in 16.3% of children, more often after a moderate form of the disease. The number of cases of gastrointestinal pathology has not changed. Diseases of the respiratory system were recorded in 4.7% of patients, skin and subcutaneous tissue – 3.5% of the examined.Conclusion. A comprehensive assessment of the health status of children after COVID-19 for 1.5 years allows us to establish a decrease in the response of the child’s macroorganism to acute respiratory infections, an increase in the number of registered comorbidities, the relationship between the severity of COVID-19 and its consequences for children.